2017
DOI: 10.1016/j.str.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystallography and Electron Microscopy of Cross- and Multi-Module Nonribosomal Peptide Synthetase Proteins Reveal a Flexible Architecture

Abstract: Nonribosomal peptide synthetases (NRPS) are macromolecular machines that produce peptides with diverse activities. Structural information exists for domains, didomains, and even modules, but little is known about higher-order organization. We performed a multi-technique study on constructs from the dimodular NRPS DhbF. We determined a crystal structure of a cross-module construct including the adenylation (A) and peptidyl carrier protein (PCP) domains from module 1 and the condensation domain from module 2, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 71 publications
4
133
0
Order By: Relevance
“…13,15,17 Residues involved in NRPS–MLP interaction in these structures were cross-referenced with the sequence alignments (Figure 3a). Among these residues, there is significant commonality between functional and nonfunctional MLPs.…”
Section: Resultsmentioning
confidence: 99%
“…13,15,17 Residues involved in NRPS–MLP interaction in these structures were cross-referenced with the sequence alignments (Figure 3a). Among these residues, there is significant commonality between functional and nonfunctional MLPs.…”
Section: Resultsmentioning
confidence: 99%
“…The NRPS fragment contains an adenylation-PCP-condensation domain, crossing the border between modules and extending to the downstream condensation domain. 63 The structure shows that no interactions exist between the adenylation domain and the condensation domain of the subsequent module. Instead the condensation domain cradles the “back face” of the carrier protein domain.…”
Section: The Biochemistry and Structural Biology Of The Nonribosommentioning
confidence: 99%
“…Indeed, this is an exciting time for the structural studies of NRPSs as many structures of multidomain proteins were determined in 2016. 56-63 This review will briefly describe the structures of individual domains and the implications of the recent structures on the necessary dynamics to transfer the substrates and intermediates between different catalytic domains (Fig. 1).…”
Section: The Biochemistry and Structural Biology Of The Nonribosommentioning
confidence: 99%
See 1 more Smart Citation
“…[4b, 5a] It was also shown that various MLPs can flexibly interact with a heterologously expressed A domain to change the kinetics of activation of its natural substrate. [6a, 8] Structural studies of MLPs [9] and MLP-A domain complexes [5g, 10] have provided insights as to how A domains interact with and are affected by MLPs. The MLP structures revealed that they contain three anti-parallel β-sheets followed by one or two α-helices.…”
Section: Introductionmentioning
confidence: 99%